Pancreatic tumor metastasis to the navel in a case with three primary tumors – case report and review of the literature - Dilek, Fatma Hüsniye; Tosun, Furkan; Atay, Arif; Dilek, Osman Nuri (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Sister Mary Joseph nodule (SMJN) is a metastasis that can occur in the umbilical region due to many tumors in the abdomen. Most of the cases are of gastrointestinal system origin and are often an indicator of poor prognosis. It can be seen in 1-3% of intraabdominal and pelvic malignancies. In the literature, around 300 studies are presented, mostly in the form of case reports. Very few (7-9%) of the cases with SMJN are from pancreatic origin. In our literature review, we found that in the majority (>90%) of SMJN cases due to pancreatic tumors, the lesions originated from the pancreatic tail and/or body, and tumor marker Ca-19.9 was very high in most cases (>90%). Aim. Here, the case of SMJN seen in a patient with three different primary tumors was discussed in the light of the literature data. Description of the case. Here, our case, whose third primary malignancy was detected in the pancreas in the PET/CT examination performed to investigate the origin of SMJN in a 68-year-old female patient who had undergone surgery due to breast in 2011 and endometrium cancers in 2018 and came with umbilical metastasis, is presented in the light of the literature data. Conclusion. As a result, in our case, which was followed up due to two primary tumors, it became important to know the origin of the SMJN that occurred due to the third primary tumor detected during the CT and PET/CT examination due to the newly emerging SMJN. It is important to know the origin and histopathological features of the SMJN in order to determine the treatment to the patient.
Keywords: breast; endometrium; multiple primary tumor; pancreas; Sister Mary Joseph’s nodule; umbilical mass